Complications following blepharoplasty. (August 2014) - Sniegowski, Matthew; Davies, Brett; Hink, Eric; Durairaj, Vikram D
<x xml:space="preserve">Abstract</x> Blepharoplasty is one of the most common surgical procedures performed in the USA for both functional improvements in the aging patient as well as aesthetic rejuvenation of the periocular region and midface. A thorough understanding of periocular anatomy, as well as a detailed pre-operative ophthalmic examination is important for a good outcome. While severe complications are rare, the surgeon performing a blepharoplasty should be aware of the possible complications and understand how to minimize them. The authors summarize known the complications of this procedure for the blepharoplasty surgeon and offer the treatment strategies when they occur.